A supervisão como interrogante da práxis analítica: desejo de analista e a transmissão da psicanálise - Broide, Emília Estivalet (2017)
In the present study, we cover the praxis of psychoanalytical supervision and it’s effects, starting with a reflection on the training of psychoanalysts and transmission of psychoanalysis. We will make a brief incursion on the history of the psychoanalytical movement, highlighting the elements that initiate the process of construction of the discipline, while we situate the supervision praxis role in this process. Then we will examine the latter developments of the praxis, beyond the scope of psychoanalytical training, to include the contribution of psychoanalytical supervision in the work with teams and professionals, of varied backgrounds and theoretical orientations, working in critical social situations in different social contexts. Our objective, throughout the research, was to highlight that the “non-knowing” is inherent and structural to supervision. It is assumed that psychoanalytical supervision is less responsible for what the supervisor teaches about a case or theory, and more by the transmission of an ethic, by the means of both the supervisor and the one being supervised upholding a “non-knowing” position. The thesis being that supervision is thus constituted as an ethical-political questioner of psychoanalytical praxis, as it allows the understanding of the limits of the clinic, theories and its formalizations, which enable the “non-knowing” to enter the stage as fuel for the supervision practice itself. The one being supervised searches for knowing and certainty in the case in question, while is the role of the supervisor to refuses the superiority over the one he supervises and thus invites commitment with the case under supervision. Therefore, the clinical case will be the conducting thread which enables unconscious and transference as operators guiding the clinical listening in contexts beyond analytical, allowing psychoanalytical discourses in the practices on public policies and in supervision of health professionals and social workers. The theoretical framework that bases the present research is the works of Freud and Lacan